The Decline of Negative Stereotype on Chinese Brand Smartphone: A Case Study on Facebook Groups - Amrullah, Abdika Taslih; Purnomo, Antonius Rahmat Pujo (Anaphora : Journal of Language, Literary, and Cultural Studies, 2023)
People’s preferences for particular brands of smartphones are inextricably linked to the variety of smartphones available in the market. As the emerging power of the world economy, China also has many smartphone brands which are highly distributed in the global market, including in Indonesia despite the negative stigma which attached to the brands. The study examines this phenomena from the scope of cultural studies using the theoretical basis of the circuit of culture (du Gay et al., 1997). The study aims to enrich the perspective on how the consumption of Chinese smartphone brands among Indonesian are regulated, produced, consumed, and represented, which further constructs the perception of how the brands’ images are perceived by the Indonesian customers. The study is conducted based on qualitative approach by observing the interaction enacted in two Facebook groups about smartphones. The analysis of the circuit of culture reveals the development of the Chinese products’ image in Indonesia. The study found that the negative image on the Chinese brands smartphones is declining among the customers. Despite the existing negative comments, the group members often recommend the Chinese brand smartphones when it comes to the functional need with affordable price. Thus, the negative perspective on Chinese brand smartphones which believed that the phones are low quality low price is promisingly shifted into worth price to performance The findings shows that Chinese smartphone brands are gaining more acceptance and positive perception among Indonesian consumers based on their affordable prices and improved quality.